Flood Tracking in the Cimeta River, West Bandung Regency - Mahesa Ismail; Muhammad Naufal; Satya Pirman Nurjaman; Muhamad Naufal Atthoriq (International Journal Labs, 2025)
The Cimeta River, located in West Bandung Regency, plays a vital role in the region’s hydrological system and supports the local community. However, the area is frequently affected by flooding caused by heavy rainfall, unplanned land use changes, and insufficient drainage capacity. This study aims to identify flood-prone critical points along the Cimeta River and analyze the contributing factors. A quantitative descriptive approach was applied using hydrological modeling with HEC-HMS and hydraulic analysis with HEC-RAS. Rainfall data from the past 15 years were used to estimate design flood discharges, which were then simulated to assess the river’s capacity. The results indicate that the peak discharge for a 50-year return period (Q50) is 155 m³/s, which exceeds the current river channel capacity and poses a risk of flooding in several river segments. The study recommends river normalization through dredging, channel widening, and bank reinforcement to reduce future flood risks. These findings are expected to support more effective and sustainable flood mitigation policies.